Advances in Transmission Electron Microscopy for the Study of Soft and Hard Matter - Carlino, Elvio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book provides readers with some examples of advanced applications of electron microscopy on organic and inorganic specimens, highlighting out how new original approaches could provide a deeper understanding of the properties of matter and how a transmission electron microscope is not only a microscope but also a flexible tool for tailoring experiments, properly suited, to the issue of interest.